Die Entwicklung des Sonderkulturanbaus im Languedoc/Südfrankreich nach dem zweiten Weltkrieg - Pletsch, Alfred (ERDKUNDE, 1977)
The lower Languedoc is one of those French regions which have been subject to a lot of structural and technical improvements in its agriculture since World War II. Natural and structural disadvantages caused a number of agricultural problems for more than two centuries. The construction of the “Canal d'irrigation du Languedoc made it possible to substitute the monoculture of wine by orchards and vegetable production (fig.1 and 2). During the last years, however, the importance of fruit- and vegetable production has diminished, while viticulture has once more increased (tab. 3 and 5, fig. 3 compared with fig. 2). There are several reason for this recent change. Very high production costs (tab. 7), difficulties in getting labour force, and the extremely high risk in fruit-production encourage many farmers to abandon risky forms of agriculture and to reorientate their production towards traditional patterns by accepting lower benefits.